Patient perspectives on acromegaly disease burden: insights from a community meeting - Shah, Shruti N.; Yuen, Kevin C. J.; Bonert, Vivien; Huang, Wenyu; Sisco, Jill; Palaty, Chrystal; Dancel-Manning, Kristen; Agrawal, Nidhi (Frontiers in Endocrinology, 2025)
ObjectiveA profound mismatch between biological and symptom control in acromegaly creates a high disease burden despite achieving optimal biological control. There is a great need to learn more about the perspectives of patients living with acromegaly.MethodsAcromegaly Community hosted a virtual meeting in January 2021 and prepared a detailed report capturing participants’ input on acromegaly symptoms and current and future treatment approaches. The findings of this report are reviewed and summarized in this study.ResultsFatigue/muscle weakness (92%) and joint pain/arthritis (90%) are the two most common and troublesome symptoms reported by meeting participants. Acromegaly negatively impacts all aspects of daily living: social interaction (49%); exercise (42%); sports/recreational activities (39%); household activities (38%); attending school or job (38%); family relationships (33%); and walking (26%). Anxiety/depression is experienced by 75% of respondents. Eighty-three percent of patients underwent pituitary surgery, and over 71% of patients require medical therapy. Patients desire future improvements in medication efficacy, tolerability, and administration; mental health resources for themselves and their families; and other multimodal approaches to address their physical symptoms, specifically hunger, weight gain, muscle weakness, and joint pains.ConclusionAcromegaly patients experience significant physical and psychological burdens despite biochemical control, highlighting the need for comprehensive and patient-centered care. In particular, the impacts on activities of daily living (ADLs) and heavy psychosocial and socioeconomic burdens are striking. We advocate for periodic screening for impacted ADLs, multidisciplinary teams to proactively address these symptoms, and call for further research on under-evaluated aspects of the disease.